Hukum Melangsungkan Perkawinan Dalam Keadaan Hamil Di Luar Nikah Perspektif Hukum Islam dan Hukum Positif (Studi Kasus di Kota Palangka Raya) - Utami, Annisa; Sartika, Puja Dewi; Fitriani, Wulan (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2025)
This research is motivated by the prevalence of people who marry in a situation where the bride is pregnant from an illicit relationship or pregnant outside of marriage. Currently, the association between men and women needs special attention because it is too free without thinking about the consequences in the future. Islam commands us to keep our eyes on those who are not mahrams. Marriage as a sacred moment and a sunatullah should be carried out according to Islamic law. Unfortunately, marriage does not become such a thing when it is done because it is pregnant outside of marriage. The marriage seems to be carried out as an effort to cover up the shame of the actions he has committed. This study aims to find out more about the law of marrying in a state of pregnancy outside of marriage based on the perspective of Islamic law and positive law. The research method used in this writing is library research with a normative approach that refers to Islamic law and positive law. The results of the research in this paper show that in the Compilation of Islamic Law, a woman who is pregnant outside of marriage can be married to the man who impregnates her. However, on the other hand in QS. An-Nisa verse 24 explains that a woman who is pregnant outside of marriage can marry a man who adulterates her or does not adulterate her. According to Ustadz Abdul Somad, who is a scholar in Indonesia, people who marry because they are pregnant have a valid marriage status, both religiously and by the state.